Shaping Possibilities: A Design Science Approach to Developing Novel Strategies - Rindova, Violina P.; Martins, Luis L. (Academy of Management Review, 2021)
The goal of strategy is not only to address a given environment, but also to change it to a firm’s advantage. In this article, we maintain that design science provides a useful theoretical foundati...